Efficacy of intravenous hydration drip versus amino acid drip in idiopathic oligohydramnios - Kumar, Priti; Kakade, Aniket S.; Mehendale, Savita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Role of intravenous hydration and amino acid infusion is well documented for the treatment of foetal growth restriction and associated oligohydramnios. The present study concentrates on the efficacy of intravenous hydration and amino acid infusions in cases of isolated oligohydramnios. Methods: 30 antenatal mothers having isolated oligohydramnios and fulfilling the inclusion criteria were selected for the study. They were randomized and administered 6 drips of normal saline or amino acid infusions. The AFI was assessed before and after the infusions. The rise in AFI, need of repeat infusions and foetal outcome was studied and analyzed. Results: The results were tabulated with respect to age of patients, gestational age, gravida status, AFI on admission and post infusions, comparison between the two groups after the 6 drips, need of repeat infusions and the maternal and perinatal outcome. Analysis of the data was performed using Chi-Square test. Conclusions: This study points towards the use of intravenous amino acids and normal saline in increasing the liquor in idiopathic oligohydramnios and proves useful in reducing perinatal morbidity and mortality and thus improving pregnancy outcomes, prolonging gestational age at time of delivery thereby improvement in weight gain. However the difference between the study groups was statistically not significant.